UN Decade on Ecosystem Restoration: key considerations for Africa. Issue 3 (2nd May 2022) - Nsikani, Mlungele M.; Anderson, Pippin; Bouragaoui, Zakher; Geerts, Sjirk; Gornish, Elise S.; Kairo, James G.; Khan, Nasreen; Madikizela, Bonani; Mganga, Kevin Z.; Ntshotsho, Phumza; Okafor‐Yarwood, Ifesinachi; Webster, Kayla M. E.; et al.
Abstract : To support and scale up global restoration efforts, the United Nations (UN) has proclaimed 2021–2030 the "UN Decade on Ecosystem Restoration." The Decade offers significant opportunities for and challenges to restoration, in particular for Africa, a continent that has a large need and potential for restoration. We thus argue that the Decade must be a success in and for Africa, and for this to happen, opportunities and challenges to achieving its goals must be promptly identified, and considered in the planning and implementation of restoration. Here, we outline six key areas that should be considered at a strategic level by African countries during the Decade. These are: (1) ensuring effective oversight and governance relevant to Africa; (2) translating the goals to meet the African context; (3) making the case for restoration amid multiple development demands; (4) growing an African restoration community of practice based on regional need; (5) collaborating to improve restoration outcomes; and (6) establishing an Africa‐relevant evidence base for restoration. We believe that these six key areas—even though they are not all novel—are currently not addressed at a level that matches the scale of the problem on the continent. Although the specific actions to be taken under each key area are dependent on the restoration context, integrating these key areas in the planning and implementation of restoration efforts will likely lead to improved restoration outcomes during the Decade.